Kesejahteraan Psikologis Pada Pendidik Pendidikan Anak Usia Dini - Sri Hartini; Rifayani Hastuti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Educators become one of the important figures in education because teachers are figures who act as educators and teachers during formal education. The welfare of educators in schools needs to always be strived for. Early childhood education (PAUD) is a process of coaching in children's growth and development from the age of 0 to 6 years, which is carried out thoroughly and includes all development by stimulating physical and spiritual development so that children develop according to their time optimally. To provide good stimulation to child development, a professional educator is needed. This study uses a form of qualitative descriptive research, where researchers try to find information that will be the topic of research by prioritizing verbal data. This study used a phenomenological approach. The results of this study showed that the well-being of the 7 subjects in the researcher is very good, it is evidenced by a good attitude of self-acceptance, personal improvement towards positivity, being able to establish positive relationships with others around him, having autonomy or being able to manage his life well and having life goals that lead to the world and the hereafter.